1999
DOI: 10.1111/1467-9507.00078
|View full text |Cite
|
Sign up to set email alerts
|

Attachment in the Indonesian Caregiving Context

Abstract: The quality of the mother-child attachment relationship, the quality of support mothers provide to their children, and characteristics of the caregiving context were examined in 46 Indonesian mother-child dyads. The distribution of attachment patterns, as assessed with the Strange Situation, showed the proportion of children classified as secure and insecure-disorganized to be comparable to the global distribution as reported in two meta-analyses. An over-representation of resistant children was found within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
(30 reference statements)
4
24
0
1
Order By: Relevance
“…The asymptomatic nature of these conditions implies that they require a professional diagnosis to be recognized. This, however, is less likely to occur in Indonesia due to the extremely limited use of health care services, especially when it comes to preventive health care such as regular medical examination (Chernichovsky & Meesook, 1986;Zevalkink, Riksen-Walraven, & Van Lieshout, 1999). Therefore, a large number of acute and mild cases remain undiagnosed, leaving only severe health conditions visible to the victims.…”
Section: Analytic Frameworkmentioning
confidence: 99%
“…The asymptomatic nature of these conditions implies that they require a professional diagnosis to be recognized. This, however, is less likely to occur in Indonesia due to the extremely limited use of health care services, especially when it comes to preventive health care such as regular medical examination (Chernichovsky & Meesook, 1986;Zevalkink, Riksen-Walraven, & Van Lieshout, 1999). Therefore, a large number of acute and mild cases remain undiagnosed, leaving only severe health conditions visible to the victims.…”
Section: Analytic Frameworkmentioning
confidence: 99%
“…Researchers have attributed this unique distribution to interdependent societal values that are often associated with more enmeshment and over-involvement. These have been found to characterize Israeli parent-child relationships (Mayseless and Scharf 2009) and may lead to ambivalent/ dependent infant behaviors (Leyendecker et al 1997;Zevalkink et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study with Japanese mothers and their infants (Takahashi 1986) had no avoidant babies in the sample (N=60), although another study (Durrett et al 1984) reported five avoidant babies (N=36). Similarly, a study with Korean mothers and their infants (Jin et al 2010) had only one baby classified as avoidant (N=87), and a study with Indonesian mothers and their babies (Zevalkink et al 1999) reported only three avoidant babies in the sample (N=46). On the other hand, a study conducted in Germany (Beller and Pohl 1986) had only two resistant babies in the sample (N=40).…”
Section: The Validity Of the Strange Situation Proceduresmentioning
confidence: 98%
“…Findings suggest that insecure infants in Asian countries are more likely to be categorized as resistant, whereas their Western counterparts are more likely to be classified as avoidant. For example, studies in Indonesia (Zevalkink et al 1999), Israel (Sagi et al 1985;Sagi and Lewkowicz 1987), Japan (Takahashi 1986;Durrett et al 1984), and Korea (Jin et al 2010) have found a higher prevalence of resistant infants compared to avoidant infants. On the other hand, in Germany (Beller and Pohl 1986;Grossmann et al 1985), the Netherlands (van Ijzendoorn 1986), and the United States (e.g., see van IJzendoorn and Kroonenberg 1988, for review), a higher proportion of infants are classified as avoidant than as resistant.…”
Section: The Validity Of the Strange Situation Proceduresmentioning
confidence: 99%